You might solve this math exam question wrong, be careful

Поделиться
HTML-код
  • Опубликовано: 2 фев 2025

Комментарии • 32

  • @wes9627
    @wes9627 Месяц назад +2

    I have never used the Lambert W() function because it is not on my calculator, but I have iteratively solved for all three real roots of this and similar equations, either by using fixed-point or Newton-raphson iteration. Everyone should become proficient in using these iterative methods to solve a wide range of nonlinear systems of equations.

    • @vencik_krpo
      @vencik_krpo Месяц назад +1

      Numerical methods are very helpful indeed (I should know, numeric computing was my Master’s specialisation). But we only use them if we can’t solve the problem directly, “statically” (i.e. on paper). Otherwise, you’re 1/ inefficient and 2/ burdened with the unavoidable numeric error. Still, kudos for knowing them… :-)

  • @nasrullahhusnan2289
    @nasrullahhusnan2289 Месяц назад

    x²=2^x --> 2ln(x)=xln(2)
    [ln(x)]/x= [ln(2)]/2
    But ln(2)/2=ln[(2²)]/2²
    =l[n(4)]/4
    Hence [ln(x)]/x=[ln(4)]/4
    Therefore x={2 4}

  • @SamanNagme
    @SamanNagme Месяц назад

    Your method gives two solutions 2 and -0.766 there should be three solutions using Lambert W function, where is the 4? I know if you solve it by not using lambert W function then you will get again two solutions as in your past video but this time it would be 2 and 4.
    The question now is: can you solve it for 2, 4 and -
    -0.766 using only One method?

  • @zawatsky
    @zawatsky Месяц назад +2

    Эволюция математика: от "да это устно решается!" до "неужели нет способа найти все корни без функции Ламберта?!".🤭

  • @slickback_was_taken
    @slickback_was_taken Месяц назад +1

    This is mental math. 😂😂

    • @simonchord1
      @simonchord1 Месяц назад

      Mentally disturbing meth😂😂

  • @Checkyourself.Physics.Math-GB
    @Checkyourself.Physics.Math-GB Месяц назад +1

    Similar problem solved without Lambert function: ruclips.net/video/NGc2sDbke34/видео.html

  • @ManojkantSamal
    @ManojkantSamal Месяц назад +9

    X=2 because if a^m=m^a, then a=m
    Another method
    X^2=2^x
    Take the log
    logx^2=log 2^x
    2.log x=x. log2
    logx/x=log2/2
    So,
    X=2

    • @ainamanicolleb
      @ainamanicolleb Месяц назад +2

      logx/x=log2/2 how did you get that?

    • @ManojkantSamal
      @ManojkantSamal Месяц назад +2

      @ainamanicolleb , Taking the antilog of the equation....

    • @боженкогеоргий
      @боженкогеоргий Месяц назад +3

      4?

    • @SEBE3835
      @SEBE3835 Месяц назад +2

      Better watch the video because you only found 1 solution of the 3.

    • @sayanrabidas3901
      @sayanrabidas3901 Месяц назад

      Your first solution is wrong because. Your solution is only valid when x=2 so you could say that a=m when a^m=m^a . But actually when exponents are same by comparison we can say bases are same but in question the base and exponents values are completely altered so you cannot use that logic a^m=m^a .

  • @easystat1929
    @easystat1929 Месяц назад

    Why divideb by 2x it's confusing

  • @CanerDeniz1
    @CanerDeniz1 Месяц назад +1

  • @rainerzufall42
    @rainerzufall42 Месяц назад +1

    (x > 0!) - ln x / x = - ln x / e^(ln x) = - ln x e^(- ln x) => W_n(- ln x / x) = - ln x, as long als ln x / x < 1 / e (for W_0 branch).
    Now, x=2 is positive and ln 2 / 2 is 0.69314... / 2 = 0.34657... and 1 / e = 0.36788..., so ln 2 / 2 < 1 / e.
    Thus follows W(- ln 2 / 2) = - ln 2 = -0.69314... and x_1 = 1 / e^W_0(-ln 2 / 2) = e^(ln 2) = 2. So much for the W_0 branch!
    ln |x| / x = ln 2 / 2 => W_k(- ln |x| e^(- ln |x|)) = W_l(- ln 2 e^(- ln 2)) = W_m(- ln 4 e^(- ln 4)), l = 0. Probably m=-1, have to check.
    The problem starts with x=4. There are reasons, why W_0 is not sufficient here!
    One is that ln 2 / 2 = 2 ln 2 / 4 = ln 2² / 4 = ln 4 / 4. There is no difference in ln x / x for x=2 and x=4. Thus you need another branch to explicitly select the solution.
    For x < 0, it's even more complicated: ln x is not available, nor is x = e^(ln x) true. You must circumvent this with a special case. As you said, something with ln |x|.
    To my own shame, I saw x=2 and x=4, but I oversaw the negative solution (that is only possible because of the even exponent!)... shit happens!

  • @rainerzufall42
    @rainerzufall42 Месяц назад +1

    Why didn't you do the same thing on the right side - immediately? (I expect, you'll do it later in the video).

    • @rainerzufall42
      @rainerzufall42 Месяц назад +1

      Okay, you didn't. My answer has moved to the comment root...

  • @johnbernardmakiling3991
    @johnbernardmakiling3991 Месяц назад +4

    I just did the trial-and-error way, it's way simpler

    • @presentnaol1364
      @presentnaol1364 Месяц назад +2

      its only work if you have simple answer as he show here for exemple but in real situation, it is way more complicated

  • @RyanLewis-Johnson-wq6xs
    @RyanLewis-Johnson-wq6xs Месяц назад +1

    X=2 X=4 X^2=2^X

  • @ManojkantSamal
    @ManojkantSamal Месяц назад +1

    Nice, A better way to shape this problem as of Lambert w function...

  • @therozer1203
    @therozer1203 Месяц назад

    How x=e^ln x ?? I didn't get it

    • @l0l_h8d_l0l5
      @l0l_h8d_l0l5 Месяц назад +1

      The e and the ln cancel out

    • @payoo_2674
      @payoo_2674 Месяц назад +2

      e^x is the inverse function of ln(x)
      ln(x) is the inverse function of e^x
      so e^ln(x) = x
      and ln(e^x) = x
      The same principle applies to Lambert's W function, which is the inverse function of xe^x
      so W(xe^x) = x

  • @zawatsky
    @zawatsky Месяц назад

    По какому алгоритму эта загадочная функция считается, так никто в итоге и не объяснил. %)

  • @giannaleoci2328
    @giannaleoci2328 Месяц назад

    x=2

  • @RealQinnMalloryu4
    @RealQinnMalloryu4 Месяц назад

    (x ➖ 2x+2). {2x+2x ➖}=4x^2 2^2x^2 1^1x^2 1x^2(x ➖ 2x+1).

  • @payoo_2674
    @payoo_2674 Месяц назад +2

    x₁ = e^(-W(-ln(2)/2)) = e^(-W(-ln(2)*(2^(-1))) = e^(-W(-ln(2)*e^ln(2^(-1))) = e^(-W(-ln(2)*e^(-ln(2))) = e^(-(-ln(2))) = e^ln(2) = 2
    x₂ = e^(-W(-ln(2)/2)) = e^(-W(-(2*ln(2))/(2*2))) = e^(-W(-ln(2^2)/4)) = e^(-W(-ln(4)*(4^(-1))) = e^(-W(-ln(4)*e^ln(4^(-1))) =
    = e^(-W(-ln(4)*e^(-ln(4))) = e^(-(-ln(4))) = e^ln(4) = 4
    x₃ = -0.766664695962123093111204422510314848006675346669832058460884376...

  • @terryhurst1973
    @terryhurst1973 Месяц назад

    x=2